2013
DOI: 10.1523/jneurosci.2973-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic α7 Nicotinic Acetylcholine Receptors Enhance Hippocampal Mossy Fiber Glutamatergic Transmission via PKA Activation

Abstract: Nicotinic acetylcholine receptors (nAChRs) are expressed widely in the CNS, and mediate both synaptic and perisynaptic activities of endogenous cholinergic inputs and pharmacological actions of exogenous compounds (e.g., nicotine and choline). Behavioral studies indicate that nicotine improves such cognitive functions as learning and memory. However, the mechanism of nicotine's action on cognitive function remains elusive. We performed patch-clamp recordings from hippocampal CA3 pyramidal neurons to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 85 publications
5
62
0
Order By: Relevance
“…This information will provide further insight into the development of therapeutic treatments for the cognitive impairments associated with schizophrenia. Along these lines, we recently found that presynaptic α7 * nAChRs, via a mechanism involving PKA, enhanced hippocampal CA3 mossy fiber glutamatergic transmission [147]. These types of studies may help to provide a mechanistic explanation for the hypothesis that nicotine enhances the mossy fiber glutamatergic transmission in the hippocampal CA3 region to compensate for a loss of synaptic connection in schizophrenic patients [148].…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…This information will provide further insight into the development of therapeutic treatments for the cognitive impairments associated with schizophrenia. Along these lines, we recently found that presynaptic α7 * nAChRs, via a mechanism involving PKA, enhanced hippocampal CA3 mossy fiber glutamatergic transmission [147]. These types of studies may help to provide a mechanistic explanation for the hypothesis that nicotine enhances the mossy fiber glutamatergic transmission in the hippocampal CA3 region to compensate for a loss of synaptic connection in schizophrenic patients [148].…”
Section: Neurodevelopmental Disordersmentioning
confidence: 99%
“…Highest expression is found in hippocampus, cingulate gyrus, lateral and medial geniculates, and the reticular nucleus of the thalamus (RTN). In hippocampus, α7nAChR-mediated release of glutamate is enhanced by the activity of protein kinase A (PKA) (Cheng and Yakel, 2014). Protein kinase A expression appears to be permanently up regulated in postmortem brain of smokers (Hope et al, 2007).…”
Section: The Alpha7 Nicotinic Acetylcholine Receptor Gene Chrna7mentioning
confidence: 99%
“…However, in many cases it is not clear whether the receptor itself is the phosphoprotein. Likewise, when receptor activation has been implicated to regulate kinase activity, it is usually assumed that channel-mediated currents (usually calcium) are required intermediates to phosphorylation events (Chatterjee et al, 2009, Cheng and Yakel, 2014, El Kouhen et al, 2009, Gubbins et al, 2010, Marrero and Bencherif, 2009, Nuutinen et al, 2006, Ren et al, 2005). Although there have been studies that have shown nAChR to be phosphorylated (Charpantier et al, 2005, Guo and Wecker, 2002, Pollock et al, 2009, Pollock et al, 2007) and their phosphorylation status to have effects on turnover, assembly, and subcellular localization (Hopfield et al, 1988, Huganir et al, 1986, Swope et al, 1999) (Yamada et al, 2010), the question remains: to what degree is there direct functional cross talk between phosphorylation sites in the intracellular domain and extracellular and transmembrane sites that regulate channel function?…”
Section: Sources Of Perspectivementioning
confidence: 99%